Social and emotional development of disadvantaged students and its relationship with academic performance: evidence from China - Huang, Chunhan; Zeng, Xiaodong (Frontiers in Psychology, 2023)
This research examined the relationships between students’ academic performance and their social and emotional skills in China, as well as the mediation pathways from the perspective of connectedness and social cognitive theory. A sample of 5,703 fourth to sixth graders from less affluent areas was investigated in a large-scale survey. The results indicated that students’ academic performance had salient positive connections with their socio-emotional skills. Structural equation modeling results revealed that both students’ perception of themselves (self-efficacy) and their relation with key persons (teacher-student relationship) played mediated roles in the association between academic achievement and social and emotional skills with the indirect path accounting for 66.66% of the total effect. This study highlights the important role of socioemotional skills in academic performance and suggests the need for further research to develop effective strategies and interventions for socioemotional development in Chinese students.